Penerapan Metode Demonstrasi Untuk Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Fiqih Kelas VII di SMP IT Nurul Fajar Desa Patumbak - Mutiara, Mutiara; Naimi, Nadlah (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This community service aims to enhance the understanding of 7th-grade students at Nurul Fajar Islamic Junior High School in Patumbak Village in the subject of Islamic Jurisprudence (Fiqih) through the application of the demonstration method. The demonstration method is employed as an interactive and participatory teaching approach to address students' difficulties in comprehending complex Fiqih concepts. Through this approach, we hope to achieve two main objectives: improving students' understanding of Fiqih teachings and motivating them to actively engage in the learning process. This research employs the qualitative Classroom Action Research method, utilizing data collection techniques such as research observation and interviews. This method involves Fiqih teachers who provide direct practical demonstrations related to challenging Fiqih concepts. Students actively participate in these demonstrations by asking questions and engaging in discussions. Additionally, the use of multimedia, such as visually-based presentations, supports the learning process.  The results of this community service project indicate that the implementation of the demonstration method effectively enhances students' understanding of the Fiqih subject. Students demonstrate improvements in their grasp of Fiqih concepts and an increased motivation to learn. These findings are further supported by higher test scores and increased student participation in class discussions.